Demographic, Clinical and Coronary Angiographic Prole of Bangladeshi Expatriates Coming from Middle-East (Ibrahim Cardiac Medical Journal, 2018)
Background & objective: Middle East (ME) countries bear a heavy burden of coronary artery disease (CAD). A good number of Bangladeshi workers every year go to ME countries for earning their livelihood. To accustom with the changed working environment of the new country, they have to change their life-style, which among others includes food behavior as well. As such they become more vulnerable to non-communicable diseases or their risk factors like, diabetes, hypertension, dyslipidaemia and CAD than ever before. A sizable portion of these workers when return to their own country carry coronary artery diseases (CADs) at an unusually low age. But the health issues of the Bangladeshi expatriates in ME are yet not well reported. This study investigates if Bangladeshi workers while staying in ME countries are accustomed to unhealthy life-style which pushes them to increased risk for CADs.Materials & Methods: This cross-sectional study was conducted on 79 male Bangladeshi expatriates in ME with CAD who underwent coronary angiogram (CAG) in Ibrahim Cardiac Hospital and Research Institute (ICHRI) in the year 2015. Detailed demographic, behavioural (particularly food behavior during their stay in ME) clinical and angiographic profile of these patients were studied. The risk factors studied were life-style, BMI, smoking habit, presence of diabetes, hypertension, dyslipidaemia and family history of CAD. The outcome variable was severity of CAD in terms of single, double and triple vessel diseases.Results: The mean age the study subjects were 47.8 ± 8.5 years. Over half (53%) belonged to low income family and 73.4% were secondary or below secondary level educated. Among them 63.3% were diabetics, 58.2% hypertensive, 59.9% dyslipidaemic, 34.2% current smoker and 54.4% overweight or obese. Over 40% used to take food at restaurant regularly or frequently with 27% having excessive carbohydrate and 30% excessive fatty food including the traditional fatty meal ‘Kapsa’. These patients presented with stable angina (40.5%), unstable angina (8.9%) or had history of myocardial infarction (50.7%). Coronary angiogram revealed 43.0% with single vessel disease (SVD), 27.9% double vessel disease (DVD) and 29.1% triple vessel disease (TVD). Prevalence of smoking was significantly higher in TVDs (56.5%) than that in DVDs (27.3%) and SVDs (23.5%) (p = 0.043). Diabetes was also more frequently associated with TVDs than do with DVDs and SVDs (p = 0.007).Conclusion: Adopting healthy life-style and early screening and management of cardiovascular risk factors in these expatriates is crucial for long term favorable outcome.Ibrahim Card Med J 2016; 6 (1&2): 8-13